Association between muscles' contractile properties and jumping performance in gymnasts - Marinšek, M.; Pavletic, M. S. (Science of Gymnastics Journal, 2020)
This study examined the association between muscles` contractile properties and jumping skill performance in gymnasts. Thirty-nine internationally experienced female (56%) and male (44%) gymnasts participated in the study. Radial displacement and contraction time of the biceps femoris, rectus femoris, vastus lateralis, vastus medialis, and erector spinae were collected to assess muscles` contractile characteristics using tensiomyography (TMG). Additionally, peak power, jump height, vertical take-off velocity, and vertical peak force in squat jump, countermovement jump, and drop jump were recorded. The TMG parameters did not predict jumping performance in our sample of female and male gymnasts. Associations between TMG parameters and jumping performance are discussed in the article.